Financial reinsurance: the effective tool of insurance company’s stability management - Lezgovko, Aleksandra (Business: Theory and Practice, 2007)
Financial reinsurance has been chosen as an object of the article, as one of the kinds of reinsurance security. The author’s object of research is theoretical substantiation and problems of practical realization of financial reinsurance operations. In the eighties of the last century, the trend of incorporation of insurance companies showed up, and as a consequence of this global process, their receptivity increased, and that provided companies with the opportunity to sustain or leave the great share of risks for themselves. Due to that, the demand for insurers’ reinsurance decreased, and this had a negative influence on development of reinsurance market. A number of large losses, which occurred in the continent of America, had substantially undercut possibilities of reinsurance. The way out of that situation could be proposals for a brand new product of reinsurance, which would raise interest in insurance companies. Financial reinsurance became that product. The objective of this article is constituted of analysis of three aspects of financial reinsurance: risk theory and its reflection in balance sheet, as well as its influence on possibility of financial stability and solvency of insurance companies, and differences and advantages of financial reinsurance against traditional reinsurance are presented. In the article there were attempts made to connect the theory and practical aspects of financial reinsurance forms and methods used nowadays. First time in Lithuanian literature the essence is revealed and definition of financial reinsurance is provided, systematic research of forms and methods of financial reinsurance is performed, trends and objections to its development are revealed. Practical significance of the findings is that the material of the article can be applied in Lithuanian insurance companies as methodical recommendations when concluding financial reinsurance contracts, since one of the main functions of traditional and financial reinsurance is improvement of financial state of insurance companies. Financial reinsurance performs not only the same functions as traditional reinsurance, but also provides an insurer with the additional financial advantage. The major task of the state is security of propriety interests of the insureds. In this respect, there is a need to acknowledge the mechanism of financial reinsurance as the one having its own place and significance for this process. Insurers’ motives classification while concluding one or another financial reinsurance contract is of an extreme significance in the article. Out of many contracts, the ones which can be really applied in current Lithuanian practice are distinguished, including those contracts the demand for which is possible only during the stage of corresponding development of insurance market.Article in Lithuanian.Finansinis perdraudimas: efektyvi draudimo kompanijos stabilumo valdymo priemonėSantrauka. Straipsnio objektu pasirinktas finansinis perdraudimas kaip viena iš perdraudimo apsaugos rūšių. Autoriaus tyrimo objektas yra teorinio pagrindimo ir finansinio perdraudimo operacijų praktinio realizavimo problemos. Šio straipsnio tikslas - išnagrinėti tris finansinio perdraudimo aspektus: rizikos teorijos ir jos atsispindėjimo balanse, taip pat jos įtakos finansinio stabilumo ir draudimo kompanijų mokumo galimybei, pateikti finansinio perdraudimo skirtumus ir pranašumus, palyginti su tradiciniu perdraudimu. Straipsnyje pabandyta susieti teoriją ir šiandien taikomų finansinio perdraudimo formų ir metodų praktinius aspektus. Pirmą kartą lietuviškoje literatūroje atskleista esmė ir pateiktas finansinio perdraudimo apibrėžimas, atliktas sisteminis finansinio perdraudimo metodų ir formų tyrimas, atskleistos tendencijos ir jo vystymosi prieštaravimai. Gautų rezultatų praktinė reikšmė yra ta, kad straipsnio medžiaga gali būti panaudota Lietuvos draudimo kompanijose kaip metodinės rekomendacijos, sudarant finansinio perdraudimo sutartis. Nes viena iš pagrindinių tradicinio ir finansinio perdraudimo funkcijų - pagerinti draudimo kompanijų finansinę padėtį. O finansinis perdraudimas atlieka ne tik šias funkcijas, kaip ir tradicinis perdraudimas, bet ir suteikia draudikui papildomą finansinį pranašumą.Reikšminiai žodžiai: finansinis perdraudimas, draudimas, perdraudimas, draudėjas, draudikas, perdraudikas.